Morphological Investigation of the Urban Form of Qom (Iran) at the Micro-scale: Spatial Distribution of Streets and Activities - Zamani Vahid; Mohammadi Mahmoud; Ghalehnoee Mahmoud (Lodz University of Technology Press, 2023)
Streets function as the interaction space for two systems of movement and activity. Street layout has influence on both distribution pattern of commercial/service (CS) activities and motorized/pedestrian traffic pattern and vice versa. Qom, a city located in central Iran with a long history of civilization, is characterised by a diverse typology of urban form and accordingly, different kinds of movement-activity patterns in the historic, middle and peripheral areas as the result of morphological, economic and social drivers. To take a step towards recognizing the patterns, this paper aims at rigorously explaining the relationship between the structural features of street layout and CS activity presence in Qom at the micro-scale, i.e. street segments, of the centralised zones through adopting a quantitative approach. After identifying ten morphologically-homogenous high-centralised superblocks – called local morphological zones (LMZs) –regarding street network centrality index of local closeness (LCNC) using Multiple Centrality Assessment (MCA), thedistribution of layout/activity elements alongside the street segments (weighted by LCNC) are investigated using Lorenz curve.Then, the distribution density datasets of layout/activity elements are modelled using Kernel Density Estimation (KDE) andanalysed by raster comparison techniques. The findings show that the linear distribution of the CS activities alongside the streetnetwork shows more relationship with LCNC rather than the street nodes. Concerning the areal distribution, the highest spatialcorrelation is found between the street nodes, i.e. three-ways and dead-ends and street segments (weighted by LCNC);furthermore, regarding street pattern, a typical historic fabric of Qom is a high-centralised area characterised by high proportionof three-ways and dead-ends, but, by low proportion of four-ways. The results are applicable in achieving the goals ofcommunity planning.
Keywords: street layout; commercial/service activities; spatial correlation; network centrality; Lorenz curve; układ ulic; działalność handlowo-usługowa; korelacja przestrzenna; centralność sieci; krzywa Lorenza